Feminist resistance to violence: coverage of radical feminist media in Turkey (2011)
Abstract: This paper aims to analyse how the radical feminist media cover the issue of violence against women and how it relates violence in a general context from militarism and state violence. Pazartesi and Amargi, two radical feminist magazines, play a significant role in the Turkish alternative media. Although the feminist critique of violence primarily covers violence against women, the feminist movement and media with the breeze of third wave feminism are not indifferent to the problem of state violence and militarism, and represent conscientious objection and the anti-war movement.